Risk factors associated with the occurrence of anthrax outbreaks in livestock in the country of Georgia: A case-control investigation 2013-2015 - Rao, Sangeeta (PLoS One, 2019)
INTRODUCTION: Anthrax is considered endemic in livestock in Georgia. In 2007, the annual vaccination became the responsibility of livestock owners, while contracting of private veterinarians was not officially required. Six years later, due to increase in human outbreaks associated with livestock handling, there is a need to find out the risk factors of livestock anthrax in Georgia. OBJECTIVE: To identify exposures and risk factors associated with livestock anthrax. METHODS: A matched case-control study design was used to recruit the owners of individual livestock anthrax cases that occurred between June 2013 and May 2015, and owners of unaffected livestock from within (“village control”) and outside the village (“area control”). We collected data about the case and control livestock animals’ exposure and risk factors within the one-month prior to the disease onset of the case livestock (or matched case for the controls). We used logistic regression analysis (univariate and multivariable) to calculate the odds ratios of exposures and risk factors. RESULTS: During the study period, 36 anthrax cases met the case definition and were enrolled in the study; 67 matched village control livestock and 71 matched area control livestock were also enrolled. The findings from multivariable logistic regression analysis demonstrate that vaccination within the last two years significantly reduced the odds of anthrax in cattle (OR = 0.014; 95% Confidence interval = <0.001, 0.99). The other factors that were significantly protective against anthrax were ‘animals being in covered fence area/barn’ (OR = 0.065; p-value = 0.036), and ‘female animal being pregnant or milking compared to heifer’ (OR = 0.006; p-value = 0.037). CONCLUSIONS: The information obtained from this study has involved and been presented to decision makers, used to build technical capacity of veterinary staff, and to foster a One Health approach to the control of zoonotic diseases which will optimize prevention and control strategies. Georgia has embedded the knowledge and specific evidence that vaccination is a highly protective measure to prevent anthrax deaths among livestock, to which primary emphasis of the anthrax control program will be given. Education of livestock keepers in Georgia is an overriding priority.